Socio-economic Inequities and Anemia in Pregnancy in Gajapati District of Odisha: An Empirical Inquest - Pattanaik, Madhuswapna; Jena, Damodar; Mishra, Priyanka; Mishra, Abha; Nayak, Bandana; Thakur, Rakesh Ranjan (Indian Journal of Information Sources and Services, 2025)
Anemia in pregnancy presents a critical public health concern in developing countries, including India, as it is associated with increased risks of maternal complications and adverse fetal outcomes. This study investigates the socio-economic and demographic variables associated with anemia during pregnancy in Gajapati district, Odisha, an aspirational district with a significant tribal population. A cross-sectional survey was carried out at the community level involving 151 pregnant women. Data were collected through semi-structured interviews, and hemoglobin levels were recorded from ‘Mother and Child Protection’ (MCP) cards issued under the National Health Mission. Statistical analysis using SPSS (v20) included descriptive statistics, bivariate analysis, and binary logistic regression. The results revealed a 37.75% prevalence of anemia, with 12.58% experiencing moderate anemia. Significant associations were found between anemia and educational level (p = 0.004), maternal age (p = 0.001), and rural residence (p = 0.007), while factors such as income and family size showed no significant impact. These findings highlight the importance of focused health education, improved access to antenatal care, and enhanced outreach through SHGs and ASHA workers in tribal and underserved areas. The study contributes to the evidence base for designing context-specific interventions aligned with national nutrition and maternal health strategies.